Effect of a cluster randomised team training intervention on adverse perinatal and maternal outcomes: a stepped wedge study. (1st March 2019) - Romijn, A; Ravelli, ACJ; de Bruijne, MC; Twisk, JWR; Wagner, C; de Groot, CJM; Teunissen, PW
Abstract : Objective: To study the effect of an intervention based on Crew Resource Management team training, including a tool for structured communication, on adverse perinatal and maternal outcomes. Design: Stepped wedge. Setting: The Netherlands. Population or sample: Registry data of 8123 women referred from primary care to a hospital during childbirth, at ≥ 32.0 weeks of singleton gestation and with no congenital abnormalities, in the period 2012–15. Methods: Obstetric teams of five hospitals and their surrounding primary‐care midwifery practices participated in the intervention. In total, 49 team training sessions were organised for 465 care professionals (75.5% participated). Adverse perinatal and maternal outcomes before, during and after the intervention were analysed using multivariate logistic regression analyses. Main Outcome Measures: Adverse Outcome Index (AOI‐5), a composite measure involving; intrapartum or neonatal death, admission to neonatal intensive care unit, Apgar < 7 at 5 minutes, postpartum haemorrhage and/or perineal tear. Results: In total, an AOI‐5 score was reported in 11.3% of the study population. No significant difference was found in the incidence of the AOI‐5 score after the intervention compared with before the intervention (OR 1.07: 95% CI 0.92–1.24). Conclusions: We found no effect of the intervention on adverse perinatal and maternal outcomes for women who were referred during childbirth. Team training is appreciated in practice, but evidence on the long‐term impact is still limited. Upcoming studies should build on previous research and consider more sensitive outcome measures. Tweetable abstract: A cluster randomised team training intervention showed no effect on adverse perinatal and maternal outcomes for women referred during childbirth. Tweetable abstract: A cluster randomised team training intervention showed no effect on adverse perinatal and maternal outcomes for women referred during childbirth.